2011
DOI: 10.1016/j.molimm.2011.07.024
|View full text |Cite
|
Sign up to set email alerts
|

Evaluating the conformation of recombinant domain I of β2-glycoprotein I and its interaction with human monoclonal antibodies

Abstract: Highlights► Bacterial expressed human recombinant DI has a structure consistent with that of DI in the published β2GPI crystal structure. ► Mutating residues D8/D9 and R39 do not alter the overall DI protein fold but cause local changes in surface contour. ► Monoclonal aPL-derived antibodies and DI of β2GPI interactions are influenced by specific arginine residues in aPL and particular epitopes in DI.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
16
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
6
3

Relationship

3
6

Authors

Journals

citations
Cited by 16 publications
(16 citation statements)
references
References 39 publications
0
16
0
Order By: Relevance
“…Polyclonal IgG from this patient has previously been shown to cause thrombosis in our mouse model [ 13 ]. Patient serum was fractionated into aDI-rich and aDI-poor fractions as follows: human recombinant hexahistidine-tagged DI was produced and purified as described previously [ 10 , 14 ]. Immobilized-nickel resin beads (Promega, Madison, WI, USA) were equilibrated with PBS (pH 7.4), followed by incubation with purified DI (50 μg DI/100 μl resin) for 30 min.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Polyclonal IgG from this patient has previously been shown to cause thrombosis in our mouse model [ 13 ]. Patient serum was fractionated into aDI-rich and aDI-poor fractions as follows: human recombinant hexahistidine-tagged DI was produced and purified as described previously [ 10 , 14 ]. Immobilized-nickel resin beads (Promega, Madison, WI, USA) were equilibrated with PBS (pH 7.4), followed by incubation with purified DI (50 μg DI/100 μl resin) for 30 min.…”
Section: Methodsmentioning
confidence: 99%
“…We previously demonstrated that human recombinant DI abrogated the thrombogenic ability of polyclonal human IgG purified from a patient with APS in our well-characterized in vivo mouse model of thrombotic APS [ 9 ], while a human monoclonal IgG aPL, IS4, both bound DI [ 10 ] and enhanced clot formation in the same model [ 11 , 12 ]. Critically, however, no study has shown that affinity-purified IgG aDI from patients with APS has a direct prothrombotic effect in vivo .…”
Section: Introductionmentioning
confidence: 99%
“…42 Subsequent cleavage with factor Xa removed the hexahistidine tag, resulting in native DI peptide.…”
Section: Methodsmentioning
confidence: 99%
“…The anti-DI antibodies were measured [40] in the same manner as human 2GPI, except the plates were coated with bacterially-expressed, conformationally correct human recombinant DI, produced by bacterial expression at University College London [41,42]. Commercially sourced positive control sera (Louisville APL Diagnostics, USA) for IgG and IgM anti-2GPI antibodies were used as calibrators for anti-DI assay.…”
Section: Elisa For Detecting Igg and Igm Anti-dimentioning
confidence: 99%